Drinking Like Everyone Else: Trait Self-Control Moderates the Association Between Peer and Personal Heavy Episodic Drinking. (16th April 2015) - Robinson, Eric; Jones, Andrew; Christiansen, Paul; Field, Matt
<x xml:space="preserve">Abstract</x> Background: Alcohol consumption often appears to be under social influence. However, we know relatively little about whether some people are particularly likely to exhibit similar drinking patterns to their peers. Objectives: Here we tested the extent to which trait social approval concerns and trait self-control are associated with the likelihood that individuals display similar heavy episodic drinking patterns to their peers. Method: One thousand and fifty-six young adults participated in an online study. We measured trait social approval concerns (the Need to Belong scale) and trait self-control (the Self-Control scale) alongside personal heavy episodic drinking and perceptions of peer heavy episodic drinking. Results: Beliefs that one's peers (other students) drank heavily were associated with heavier personal episodic drinking. This relationship was moderated by trait self-control: The correlation between personal heavy episodic drinking and perceived peer drinking was much stronger in those with low self-control compared with those with high self-control. Contrary to hypotheses, trait social approval concerns did not moderate the relationship between perceived peer drinking and personal heavy episodic drinking. Conclusions: Social norms about drinking could act as a form of informational cue for one's own alcohol consumption, but the extent to which individuals follow or override this cue may depend on individual differences in self-control.